Enhancing the Bioavailability of Resveratrol: Combine It, Derivatize It, or Encapsulate It? - Mohamed Salla; Nadine Karaki; Belal El Kaderi; Abeer J. Ayoub; Samar Younes; Maya N. Abou Chahla; Shairaz Baksh; Sami El Khatib (MDPI AG, 2024)
Overcoming the limited bioavailability and extensive metabolism of effective in vitro drugs remains a challenge that limits the translation of promising drugs into clinical trials. Resveratrol, despite its well-reported therapeutic benefits, is not metabolically stable and thus has not been utilized as an effective clinical drug. This is because it needs to be consumed in large amounts to overcome the burdens of bioavailability and conversion into less effective metabolites. Herein, we summarize the more relevant approaches to modify resveratrol, aiming to increase its biological and therapeutic efficacy. We discuss combination therapies, derivatization, and the use of resveratrol nanoparticles. Interestingly, the combination of resveratrol with established chemotherapeutic drugs has shown promising therapeutic effects on colon cancer (with oxaliplatin), liver cancer (with cisplatin, 5-FU), and gastric cancer (with doxorubicin). On the other hand, derivatizing resveratrol, including hydroxylation, amination, amidation, imidation, methoxylation, prenylation, halogenation, glycosylation, and oligomerization, differentially modifies its bioavailability and could be used for preferential therapeutic outcomes. Moreover, the encapsulation of resveratrol allows its trapping within different forms of shells for targeted therapy. Depending on the nanoparticle used, it can enhance its solubility and absorption, increasing its bioavailability and efficacy. These include polymers, metals, solid lipids, and other nanoparticles that have shown promising preclinical results, adding more "hype" to the research on resveratrol. This review provides a platform to compare the different approaches to allow directed research into better treatment options with resveratrol.